(De)Constructing the Myth of the North in British Cinema (1959-2019) - Anne-Lise Marin-Lamellet (Revue Française de Civilisation Britannique)
The British North has featured regularly on screen since 1959. The representation of its industrial and urban features has given birth to a two-pronged mythical construction over sixty years: a geographical and a psychoanalytical/gendered one using the figure of the Northerner. Cinema is a myth and identity maker but it is also a medium which has reflected the socioeconomic evolutions of the North, first synonymous with relative prosperity and modernity until the 1980s, then decline and recession owing to deindustrialisation. Simultaneously, films try to deconstruct both the archetypal North – which ends up being geographically and socioeconomically more diverse than it first seems to be – and the figure of the Northerner – who takes his self-proclaimed image or the one that the South seeks to give him with a pinch of salt. The common identity of Northerners mostly channelled through their common aversion towards the South nonetheless leads them to reconstruct the myth of their native North.